Determinants of Financial Distress Using a Binary Approach: Evidence from Property and Real Estate Firms on the IDX (2014–2023) - Ida Ayu Fatmayuni; Rina Susanti; Aditya Wardana (Equivalent : Journal of Economic, Accounting and Management, 2026)
The study explores factors that influence the probability of distress on IDX. The study focuses on property and real estate companies. The study measures distress, with a dummy variable, where 1 mark a distressed firm and 0 marks a healthy firm. I looked at profitability, liquidity, solvency and efficiency ratio as indicators. The study used a targeted sampling method to select 36 issuers observed from 2014 to 2023. I tested the relationship, between ratios and financial distress using a regression model. I see that the results show the profitability reduces the chance of the distress. I notice that when the profitability is higher the chance that a firm will face the distress goes down. I see that the liquidity raises the chance of the distress. I notice that when the liquidity is higher, in this sector the liquidity may point to working capital management. I find that the solvency does not change the chance of the distress. I find that the efficiency ratio does not change the chance of the distress either. I see that the findings show the profitability and the liquidity matter for predicting the distress, in the property and real estate industry. I find the study gives information for the investors the creditors and the regulators. The study helps the investors; the creditors and the regulators check the stability and find the warning signs.